2016
DOI: 10.1109/tevc.2015.2451701
|View full text |Cite
|
Sign up to set email alerts
|

Simple Probabilistic Population-Based Optimization

Abstract: A generic scheme is proposed for designing and classifying simple probabilistic population based optimization algorithms that use principles from Population-based Ant Colony Optimization and Simplified Swarm Optimization for solving combinatorial optimization problems. The scheme, called Simple Probabilistic Population Based Optimization scheme, identifies different types of populations (or archives) and their influence on the construction of new solutions. The scheme is used to show how Simplified Swarm Optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…For simplicity, we directly cite the results of these two winners from the corresponding competitions (CEC'2013 4 and CEC'2015). 5 Tables SXXIV-SXXVIII in the supplementary material present the comparison results with respect to PR and SR between LAMS-ACO and these two winners with each table associated with one accuracy level. The best PR results are highlighted in bold in these tables and the last row (b/e/w) 6 of these tables counts the number of functions on which LAMS-ACO is better than, equivalent to or worse than the compared winner, respectively.…”
Section: E Comparisons With Winners Of Cec Competitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For simplicity, we directly cite the results of these two winners from the corresponding competitions (CEC'2013 4 and CEC'2015). 5 Tables SXXIV-SXXVIII in the supplementary material present the comparison results with respect to PR and SR between LAMS-ACO and these two winners with each table associated with one accuracy level. The best PR results are highlighted in bold in these tables and the last row (b/e/w) 6 of these tables counts the number of functions on which LAMS-ACO is better than, equivalent to or worse than the compared winner, respectively.…”
Section: E Comparisons With Winners Of Cec Competitionsmentioning
confidence: 99%
“…From Tables SXXIV-SXXVIII in the supplementary material, we can get the following findings. 4 https://github.com/mikeagn/CEC2013/tree/master/NichingCompetition 2013FinalData 5 https://github.com/mikeagn/CEC2013/tree/master/NichingCompetition 2015FinalData 6 In this experiment, owing to the absence of the detailed results of these two winners in each run in the corresponding competitions, whether LAMS-ACO is better than, equivalent to or worse than the compared winners is judged just by the averaged PR results without any statistical test analysis. Thus, to tell apart from the results in the last section, the number of the functions on which LAMS-ACO is better than, equivalent to or worse than the compared winner, is respectively, denoted by "b/e/w" instead of "w/t/l".…”
Section: E Comparisons With Winners Of Cec Competitionsmentioning
confidence: 99%
“…In this study several evolutionary computation methods have been benchmarked and it was concluded that PACO is the method of choice. Several variants of PACO for the TSP have been investigated recently in [11].…”
Section: Background and Related Liter-aturementioning
confidence: 99%
“…Population-based evolutionary optimizations, initially inspired by biological process, are considered as a major way of solving complex optimization problems. In the past few decades, a number of population-based evolutionary algorithms are proposed such as simulated annealing (SA), differential evolution (DE), Artificial Immune System(AIS) [2,3], particle swarm optimization (PSO), bee colony optimization (BCO), genetic algorithms (GAs), populationbased increamental learning (PBIL) and ant colony optimization (ACO) [4]. Among them, SA, DE, PSO and BCO are roughly proposed to find solutions in continuous domains mainly for function optimization while GA, PBIL and ACO are mainly used for solving combinatorial optimization problems [5].…”
Section: Introductionmentioning
confidence: 99%